Hyperammonemia secondary to asparaginase: A case series. (February 2016) - Nussbaum, Vicki; Lubcke, Nicole; Findlay, Russell
Objective: To report on hyperammonemia noted in a series of patients receiving asparaginase products at our institution. Summary of cases: We present four patients who experienced symptomatic hyperammonemia after receiving either pegaspargase (three patients) or Erwinia asparaginase (one patient). Presenting symptoms included lethargy, difficulty awakening, confusion, dizziness, numbness and tingling, hallucinations, and paranoia. All patients were treated with lactulose, which led to a decrease in ammonia level and resolution of symptoms. Discussion: Hyperammonemia secondary to asparaginase products has been reported in the literature. The signs and symptoms of increased ammonia should be included in consent documents and discussed with patients and their families. Monitoring of ammonia or asparagine levels may help individualize therapy with asparaginase products in the future. Conclusion: Hyperammonemia can occur during treatment of acute lymphoblastic leukemia with asparaginase products. Lactulose appears to be a useful treatment strategy. Further study is warranted to determine whether dose modifications are required for pegaspargase in some patients. Whether these dose modifications would be in the dose itself or frequency of administration remains to be determined.